2021
DOI: 10.1016/j.msec.2021.112114
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of magnesium doped sol-gel biomaterial for bone tissue regeneration: The effect of Mg ion in protein adsorption

Abstract: Magnesium is the fourth most abundant element in the human body with a wide battery of functions in the maintenance of normal cell homeostasis. In the bone, this element incorporates in the hydroxyapatite structure and it takes part in mineral metabolism and regulates osteoclast functions. In this study, sol-gel materials with increasing concentrations of MgCl2 (0.5, 1, and 1.5%) were synthesized and applied onto Ti surfaces as coatings. The materials were first physicochemically characterized. In vitro respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…In vitro inflammatory response to Ca depends on the ion concentration in a material, 20 while Mg generally shows an antiinflammatory activity. 10 Here, the CaMg sol-gel coatings displayed increased TNF-α and TGF-β secretion and gene expression. However, these coatings decreased IL-10 expression in the Mg-dose-dependent manner.…”
Section: Papermentioning
confidence: 82%
See 2 more Smart Citations
“…In vitro inflammatory response to Ca depends on the ion concentration in a material, 20 while Mg generally shows an antiinflammatory activity. 10 Here, the CaMg sol-gel coatings displayed increased TNF-α and TGF-β secretion and gene expression. However, these coatings decreased IL-10 expression in the Mg-dose-dependent manner.…”
Section: Papermentioning
confidence: 82%
“…The individual effects of these two ions on the protein adsorption on implant surfaces have been already examined. 10,20 It has been shown that Ca has a high affinity to proteins involved in coagulation and inflammatory responses, while the addition of Mg increases the material affinity to proteins related to cell adhesion. With these data in mind, designing and analysing a biomaterial to combine the regulatory properties of the two ions was a promising path to follow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al 49 showed that the surface of osteoblastic cells increases with a Mg 2+ concentration up to 8 mM (7.6 mM found at maximum in our study) prior to diminishing which is in accordance with another recent study that depicted the same dependence of the size on Mg 2+ ions, based on the argument that a lot of proteins, proteases, or apolipoproteins are prone to adsorb onto material surfaces in the presence of less than 10 mM Mg 2+ . 63 Likewise, protein adsorption may provide several sites to support cell adhesion and the establishment of focal contacts. Moreover, MC3T3-E1 cells in Mg 1% displayed the polygonal morphology whereas they appeared smaller and spindle-shaped in Mg 1.5%.…”
Section: Resultsmentioning
confidence: 99%
“…17 Proteomics offers powerful tools for analysing complex mixtures of proteins, such as the protein layers formed on biomaterials. 18 Cerqueira et al 19 have studied the protein layers adsorbed onto magnesium-enriched surfaces. Many proteins associated with cell adhesion were found on these surfaces, explaining the improved osteoblast adhesion to these Mg-enriched materials.…”
Section: Introductionmentioning
confidence: 99%